General relativistic theory of gravity and electricity - Valenzuela, Mississippi (2022)
As gravitation and electromagnetism are closely analogous long-range interactions, and the current formulation of gravitation is given in terms of geometry, we expect the latter also to appear throug the geometry. We look for the formally most simple expression for the law of gravitation in the absence of an electromagnetic field, and then the most natural generalization of this law. This theory contain Maxwell theory in first approximation. In the following we outline the scheme of the general theory and then show in which sense this contains the law of the pure gravitational field and Maxwell theory.